Changes in Kidney Function and in the Rate of Tubular Dysfunction After Tenofovir Withdrawal or Continuation in HIV-Infected Patients. (1st August 2016) - Casado, José L.; del Rey, Jose M.; Bañón, Sara; Santiuste, Carmen; Rodriguez, Mar; Moreno, Ana; Perez-Elías, María J.; Liaño, Fernando; Moreno, Santiago
Abstract : Introduction: Longitudinal data on the changes in kidney function and tubular abnormalities in case of tenofovir disoproxil fumarate (TDF) withdrawal or continuation are scarce. Methods: Prospective study of 228 patients receiving TDF, with 3 sequential determinations of serum creatinine, estimated glomerular filtration rate (eGFR), phosphatemia, and different urinary parameters (protein, albumin, phosphaturia, uricosuria, and glycosuria). Changes were analyzed in patients who interrupted TDF as compared to those who continued the same regimen. Proximal renal tubular dysfunction (PRTD) was defined as ≥2 tubular abnormalities. Results: After a median follow-up of 59.5 months, 78 patients (34%) had PRTD, mainly proteinuria (40%) and phosphaturia (61%), and time on TDF explains the severity of tubular alterations and eGFR slopes. In 35 switching patients, there was a rapid and significant eGFR improvement (median +4.1 ml/min per 1.73 m 2 ; P = 0.02), leading to a 39%–83% reduction in the prevalence of tubular abnormalities and of PRTD in less than 1 year (66%–39%). In comparison, 193 patients continuing the same regimen for 21.2 months had a small but significant and progressive eGFR decrease (−2.9 mL·min −1 ·1.73 m −2 ; P < 0.01), and a progressive rise in the prevalence of phosphaturia, uricosuria, and glycosuria (+9%–56%). In linear mixed-effect model, subsequent eGFR impairment was associated with proteinuria and time on TDF, and eGFR improvement with TDF discontinuation. Conclusions: Our data support the role of use and time on TDF in eGFR decline and tubular dysfunction. In contrast, TDF withdrawal is followed by a rapid and significant, although partial, recovery of eGFR and tubular abnormalities.